Review article: clinical pharmacology of current and investigational hepatitis B virus therapies. Issue 2 (16th December 2019) - Smolders, Elise J.; Burger, David M.; Feld, Jordan J.; Kiser, Jennifer J.
Summary: Background: Treatment of hepatitis B virus (HBV) infection with current therapy suppresses HBV DNA, but loss of hepatitis B surface antigen (HBsAg; functional cure), is rare. Multiple compounds are under investigation. Aims: To describe the pharmacology, including drug interactions, efficacy, safety and mechanisms of action of investigational compounds for HBV infection. Methods: Descriptive review using PubMed and Google to identify literature/conference papers on investigational compounds (≥Phase 2) with data on efficacy and safety in HBV‐infected patients. Results: Bulevirtide, JNJ‐56136379, ABI‐H0731, REP‐2139, and inarigivir decrease HBV DNA/RNA, with greater potency than current nucleos(t)ide analogues. REP‐2139 (25%‐75% of patients, 20‐48 weeks treatment) and inarigivir (26% of patients, 12‐24 weeks treatment) induce HBsAg loss. ARO‐HBV reduced (>1.5 log10 UI/mL) HBsAg in 85% of patients (12 weeks treatment). There are some safety concerns with investigational agents (e.g., increased bile acids with bulevirtide, and liver enzyme flares with REP‐2139) which will require a risk benefit assessment compared with current therapies. Single and multidose pharmacokinetic data are available for bulevirtide, JNJ‐56136379, ABI‐H0731; no such data are available for REP‐2139, ARO‐HBV, inarigivir. Initial drug interaction assessments have been performed with bulevirtide and inarigivir (only in vitro). Conclusions: There are promising investigational therapies for HBV infection. Increasing the potential for HBsAg loss may result in more patients achieving functional cure. However, many knowledge gaps remain such as pharmacokinetics in those with HBV, cirrhosis and renal impairment but also the interaction potential between investigational therapies, risk‐benefit profiles, and potential for drug interactions with medications used to treat comorbidities associated with aging.